ESSENTIAL CHARACTERISTICS OF AN ERP SYSTEM : CONCEPTUALIZATION AND OPERATIONALIZATION - Sylvestre Uwizeyemungu; Louis Raymond (Journal of Information and Organizational Sciences, 2012)
The interest of firms in ERP systems has been echoed in both the scientific andprofessional literature. It is worth noting however that while this literature has becomeincreasingly abundant, there does not yet exist an operational definition of the ERP conceptthat is, if not unanimously, at least widely accepted. This constitutes a handicap for boththe research and practice communities. The present study outlines what could beconsidered as an ERP by first determining the essentially required characteristics of such asystem: integration, flexibility and transversality. Indicators are then provided in order tooperationalise these three characteristics. The study concludes by proposing a researchframework on the impact of an ERP’s key characteristics upon the performance of thesystem in a given organisational setting.